International legal framework on the prevention of vessel-source pollution - LIU, Nengye (Institutional Knowledge at Singapore Management University, 2010)
T h is paper exa mi ne s the international legal f r a m e w o r k of the prevention of vessel-source marine pollution. It provides an overview of current international framework. First-the study introduces International Maritime Organization (IM O ) and the Law of the Sea Convention (LO SC ). Second-it analyzes the relation between Conventions adopted under the auspices of the IMO (IMO Conventions) and the LOSC. Third.it discusses major IMO Conventions dealing with prevention of vessel-source pollution. Finally, this paper addresses challenges of the international legal framework.